Violence in a Post-Conflict Context : Urban Poor Perceptions from Guatemala - Moser, Caroline; McIlwaine, Cathy (Washington, DC: World Bank, 2013)
The study documents how people living in poor urban communities in Guatemala perceive violence. Specifically, it identifies the categories of violence affecting poor communities, the costs of different types of violence, the effects on violence on social capital, the interventions employed by people to deal with violence, and the causes and effects of social exclusion. The study develops a violence-capital-exclusion nexus which is an analytical framework linking different types of violence both to society's capital and to the exclusion of its poor population. To incorporate the rarely heard voices of the poor, the study uses participatory urban appraisal methodology, which emphasizes local knowledge and enables local people to analyze the problems they face and identify their own solutions. Local-level recommendations for reducing violence can be summed up in terms of six priorities: Rebuild trust in the police and judicial system. Attack the problem of alcoholism. Reduce society's tolerance for intrafamily violence. Prevent the spread of drug consumption. Transform maras (violent youth gangs) from perverse to productive social organizations. Develop mechanisms to build sustainable community-based membership organizations.